« Ne diriez-vous pas qu’il s’agit là de propagande ? » Le programme d’information internationale des États-Unis en débat (1945-1947) - Raphaël Ricaud (Transatlantica)
In the aftermath of the Second World War, the United States dismantled its Office of War Information. Peace having returned, such an agency did not fit the democratic ideal well. Nonetheless, as America put on its new world-leader mantle, she realized a new international information program would be necessary. In order for the American people to accept such a program, notions such as democratic proselytizing, journalism, free competition, and legal advocacy replaced propaganda.